Pengembangan Instrumen Asesmen Literasi Digital dalam Pembelajaran untuk Guru Madrasah Ibtidaiyah - Hana Lestari; Ima Rahmawati (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to develop a digital literacy instrument for Madrasah Ibtidaiyah teachers that serves to measure the extent of teachers' digital literacy. This research involved 166 teacher respondents in MI in Bogor City. The research method used is the Plomp Model, also known as design research, which has stages such as preliminary research, prototyping phase, and assessment phase in the development process. The instrument developed in the form of a questionnaire that has been made is first validated by 2 expert validators (material and evaluation), after being declared valid by expert validators, the questionnaire is then carried out a limited test to calculate the level of validity and reliability of each question item. The questionnaire uses a Likert scale with 4 categories of answer choices (often, rarely, ever, never). The results of the study can be concluded that The question items that can be used as data collection tools on the digital literacy questionnaire instrument are 50 question items and are categorized as valid and can be used as a teacher digital literacy evaluation tool. Based on the validity calculation, it can be seen that 78% of the question items can be used as data collection tools with high and sufficient validity categories. While the other 22% can be used by making improvements first with low validity. Based on reliability criteria, the digital literacy questionnaire shows very high-reliability criteria (0.860) with a reliability level greater than 0.7.